Role of Endothelial Cells in Acute and Chronic Thrombosis - Bochenek, Magdalena L.; Schäfer, Katrin (Hämostaseologie, 2019)
Haemostasis encompasses a set of strictly regulated actions, such as vasoconstriction, platelet activation and blood coagulation. Endothelial cells play a crucial role in all of these processes and are an integral part of the vascular response to injury resulting in thrombus formation. Healthy endothelium expresses mediators to prevent platelet activation, including prostacyclin and nitric oxide, and to inhibit coagulation, such as thrombomodulin or RNase1. Upon activation, endothelial cells expose von Willebrand factor, integrins and other receptors to interact with activated platelets, erythrocytes and coagulation factors, respectively, resulting in blood clot formation. The endothelial cell response to cytokines and growth factors released from activated platelets and immune cells abundantly present in arterial and venous thrombi also plays an important role for thrombus resolution, whereas failure to completely resolve thrombi may initiate fibrotic remodelling and chronic vascular occlusion both in the arterial and venous tree. Therefore, endothelial cells are increasingly recognized as potential target to prevent thrombotic events and to accelerate thrombus resolution. Here, we discuss recent publications from our group in the context of other studies on the role of the endothelium during acute and chronic thrombotic events.
Keywords: arterial; endothelial dysfunction; thrombosis; thrombus resolution; venous